Mari of Udmurtia: Factors of Preserving Traditional Culture in Modern Conditions - I. L. Pozdeev (Научный диалог, 2021)
The factors of preservation and intergenerational transmission of the traditional culture of the local group of Mari living in the territory of Udmurtia in a different ethnic environment is examined in the article. The source basis of the article was the field ethnographic materials collected in 2007 among the Mari of the Karakulinsky region of the Udmurt Republic and introduced into scientific circulation for the first time. The socio-economic situation of the respondents, the established mechanisms of adaptation to market relations, the preservation of traditional rituals and holidays, material and spiritual culture, the use of the native language, ethno-demographic processes, the activities of the Mari community to support ethnic culture are showed in the work. The author notes that the historically formed mechanism for ensuring the viability of the Mari society includes practices of demographic behavior, ethnic socialization of youth, reproduction of elements of spiritual and religious culture (prayers, family and calendar rituals, songs) and the material world (national costume, elements of architecture, musical instruments, national cuisine), the use of the Mari language. It has been proven that the ritual sphere of the Mari is undergoing transformations, but at the same time it continues to remain an inseparable part of the life of the people. In the course of the work, it was also revealed that the local group of Mari in modern conditions for self-preservation needs to constantly generate ethnic markers based on traditional culture. The key role in this is assigned to the village community, educational institutions and public organizations.